A new species of Misetus Wesmael, 1845 (Hymenoptera, Ichneumonidae, Ichneumoninae, Phaeogenini) from Italy, with updated key to the females of Palaearctic species - Giovanni, Filippo Di; Scaramozzino, Pier Luigi; Diller, Erich (Zootaxa, 2018)
A new species, Misetus strumiai sp. n., from the island of Montecristo (Italy, Tuscany) is described and illustrated. The new species is characterized by having the clypeus with a small median tooth, metasomal tergite II almost entirely smooth and polished, and extensively red body color (except for black head). A comparative diagnosis is provided in order to distinguish the new taxon from the other known species of the genus Misetus Wesmael, 1845.